Вплив інженерії легування та просторової конфігурації структури на енергетичну ефективність фотоперетворювачів ZnO/POROUS-Si/Si - Носань, Сергій Вікторович; Дяденчук, Альона Федорівна; Nosan, Serhii; Dyadenchuk, Alona (Запоріжжя : Видавничій дім «Гельветика», 2026)
UA: У роботі досліджено вплив концентрації легування й товщини шарів на енергетичну ефективність фотоперетворювачів на основі гетероструктури ZnO/porous-Si/Si. За допомогою моделювання в середо вищі PC1D проаналізовано зміну фотогенерації, рекомбінаційних процесів і параметрів ВАХ залежно від варіації товщини шарів ZnO й поруватого кремнію, а також рівня легування ZnO. Установлено, що оптимальні значення товщини ZnO (10 мкм) і porous-Si (1 мкм), а також концентрація легування ZnO на рівні 1019 см-3 забезпечують максимальну ефективність перетворення 22,6 %. Показано, що надмірне легування призводить до зростання рекомбінаційних втрат і зниження продуктивності. Отримані результати можуть бути використані для оптимізації конструкції високоефективних фотоперетворювачів на основі кремнієвих гетероструктур. /// EN: This paper presents a comprehensive study of the influence of doping engineering and layer-thickness optimization on the energy conversion efficiency of ZnO/porous-Si/Si heterostructure-based photovoltaic devices. Using the PC1D simulation environment, the research examines how variations in the thickness of ZnO and porous silicon layers, as well as changes in the doping concentration of the ZnO film, affect photogeneration, recombination dynamics, and the resulting current–voltage characteristics. The modeling results demonstrate that the interplay between optical absorption, carrier transport, and recombination processes is highly sensitive to both geometric and doping parameters of the structure. It was established that the optimal configuration – ZnO thickness of 10 μm, porous-Si thickness of 1 μm, and ZnO doping concentration of 1019 cm-3 – provides the highest simulated conversion efficiency of 22.6 %. Increasing the ZnO thickness beyond this range leads to reduced performance due to enhanced bulk recombination, while excessive doping results in a significant decrease in minority-carrier lifetime and overall device efficiency. The study highlights the importance of balancing optical and electrical properties when designing heterostructure-based solar cells, particularly those incorporating porous silicon as a functional buffer layer. The obtained results contribute to a deeper understanding of the mechanisms governing the operation of ZnO/porous-Si/Si photoconverters and demonstrate the potential of structural and doping optimization for improving the performance of silicon-based photovoltaic technologies.
Influence of doping engineering and spatial structure configuration on the energy efficiency of ZnO/POROUS-Si/Si photoconverters
Keywords: гетероструктура; легування; товщина шарів; PC1D; фотоперетворювач; heterostructure; doping; layer thickness; photoconverter